232. Do Antibiotic Timeouts Improve Antibiotic Utilization?. (26th November 2018) - Kinn, Patrick; Postelnick, Michael; Kuper, Kristi; Gibson, Amanda; Pakyz, Amy; Schulz, Lucas T
Abstract: Background: The antibiotic timeout (ATO) is a stewardship tool that protocolizes review of objective clinical data after a predefined period of time and encourages antimicrobial regimen re-assessment. Methods: Vizient member hospitals were utilized to recruit a variety of acute healthcare institutions, including institutions with and without an ATO process. Participating institutions submitted de-identified patient-level antibiotic therapy courses from a single day within a 5-week window to create a snapshot of overall antibiotic utilization. Therapy courses were evaluated on metrics including the prevalence of anti-pseudomonal agents, agents active against methicillin-resistant Staphylococcus aureus (MRSA), and oral (vs. intravenous) antibiotics. The outcome measures included: percent changes in prevalence of courses with antipseudomonal and anti-MRSA agents after day 3, and percent change in antibiotics ordered for oral administration after day 3. These outcome measures were compared between ATO institutions and non-ATO institutions. Results: A total of 6, 184 antibiotic therapy courses were collected from 61 participating institutions (17 ATO institutions; 44 non-ATO institutions). Of 71 institutions that completed enrollment survey, 10 did not complete submission of therapy course data. Antibiotic courses prescribed for prophylaxis ( n = 975) and courses that extended beyond 7 days ( n = 1, 192) were excluded from analysis, resulting in an analysis group that included 4, 017 therapy courses (1, 396 from ATO institutions vs. 2, 621 from non-ATO institutions). The prevalence of patients receiving anti-pseudomonal agents increased after day 3 by 3.03% ( P = 0.28) at ATO institutions and decreased 0.45% ( P = 0.84) at non-ATO institutions. The prevalence of patients receiving anti-MRSA agents decreased after day 3 by 2.16% ( P = 0.41) at ATO institutions and decreased 5.05% ( P = 0.005) at non-ATO institutions. Oral antibiotic use increased after day 3 by 3.09% ( P = 0.08) at ATO institutions while use at non-ATO institutions increased 7.99% ( P = 0.0001). Conclusion: Antibiotic therapy course data collected across multiple sites provided no evidence for improved antimicrobial utilization among institutions that have implemented an antibiotic timeout compared with institutions without a timeout. Disclosures: All authors: No reported disclosures.